Islamic Education Management: The Development of Sharia Accounting Practicum Teaching Materials - Citradewi, Adelina; Hadi, Nor; Ahmad, Sarimah (Pascasarjana IAIN Kudus, 2025)
The limited literature on Sharia accounting practicums in Indonesia that align with Sharia financial accounting standards is a phenomenon of significant concern. The Sharia Accounting Practicum course is a compulsory course for students in the Sharia Accounting Study Program at UIN Sunan Kudus and several other religious universities within the Ministry of Religion. This study aims to develop a learning product in the form of Sharia Accounting Practicum teaching materials using the research and development (R&D) method. The subjects of this study were students in the Sharia Accounting Study Program at UIN Sunan Kudus who had taken the Sharia Accounting Practicum Course. Material experts and media experts among the faculty served as validators to assess the feasibility of the teaching materials. This study used a questionnaire to collect data. Qualitative descriptive analysis was used to analyze the data through data presentation and verification. The validity and effectiveness analysis of the respondents as a whole yielded a result of 88.3%. Based on these results, it can be concluded that the teaching materials are highly feasible for use in the learning process.